2012
DOI: 10.1100/2012/385840
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Cellular Bcl-2 in the Progression of Hamster Cholangiocarcinogenesis

Abstract: Bcl-2 is an intracytoplasmic and membrane-associated apoptosis suppressor, and its overexpression is closely associated with survival of malignant tumors, in particular their aggressive behavior and poor prognosis. The role of Bcl-2 is, however, still controversial in cholangiocarcinogenesis because of the discrepancies in the expression of the protein. In the present study, alteration in the expression of Bcl-2 in cholangiocarcinogenesis was investigated by studying the immunoreactivities of this protein in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We examined potential mechanisms of action of MTDH/AEG-1 in BUC by exploring the relationship between the expression of MTDH/AEG-1 and that of seven other common biomarkers: caspase-3, Bcl-2, VEGF, Ki-67, PCNA, p53, and DcR3. Sequential activation of caspase-3 plays a central role in cell apoptosis,44 the Bcl-2 gene can inhibit tumor cell apoptosis,4547 and VEGF production by cells can stimulate vasculogenesis and angiogenesis 48,49. Ki-67 and PCNA are classical markers of cell proliferation and are routinely used by pathologists,50 whereas p53 is related to DNA repair and apoptosis 47,51.…”
Section: Discussionmentioning
confidence: 99%
“…We examined potential mechanisms of action of MTDH/AEG-1 in BUC by exploring the relationship between the expression of MTDH/AEG-1 and that of seven other common biomarkers: caspase-3, Bcl-2, VEGF, Ki-67, PCNA, p53, and DcR3. Sequential activation of caspase-3 plays a central role in cell apoptosis,44 the Bcl-2 gene can inhibit tumor cell apoptosis,4547 and VEGF production by cells can stimulate vasculogenesis and angiogenesis 48,49. Ki-67 and PCNA are classical markers of cell proliferation and are routinely used by pathologists,50 whereas p53 is related to DNA repair and apoptosis 47,51.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is an intracytoplasmic and membraneassociated apoptosis suppressor (antiapoptotic protein) gene that is found in human and canine cells, and its overexpression is closely associated with the survival of malignant tumors, in particular their aggressive behavior and poor prognosis (11,12). Apoptosis is triggered by the release of proapoptotic molecules from the mitochondria by multiple mechanisms, including maintenance of mitochondrial membrane integrity and binding to proapoptotic members of the Bcl-2 family (13).…”
Section: Lectinsmentioning
confidence: 99%
“…Bcl-2 is antiapoptotic and its overexpression (Bcl-2-Bcl-2) results in apoptosis inhibition and cell survival, whereas Bax is proapoptotic ( 9 , 10 ), and its overexpression (Bax-Bax) leads to cell death. However, the expression of the apoptosis suppressor gene Bcl-2 is low or nonexistent in hepatoma cells ( 11 , 12 ), whereas Bax is widely distributed in various organs including normal liver tissues, which indicates that Bax is probably an important apoptosis-regulating gene ( 13 ). Bai et al ( 14 ) reported the abnormal expression of Bax in Hodgkin's disease.…”
Section: Introductionmentioning
confidence: 99%